Impact of lifestyle behaviors on the development of lifestyle diseases: A retrospective cohort study - Takafumi Okawa; Hikaru Negishi; Yuki Aoki; Mitsuo Uchida; Yumi Sato; Mai Ishikawa; Rie Matsui; Kaori Hotta; Takayuki Saitoh (PLoS ONE, 2025)
Background Questionnaires are used to collect data on lifestyle behaviors during specific health checkups; however, the results cannot conclusively determine whether the behaviors influence the onset of lifestyle diseases. By analyzing data from a retrospective cohort, this study aimed to determine the specific lifestyle behaviors that most strongly contribute to the onset of lifestyle diseases, such as metabolic syndrome, hypertension, diabetes, and dyslipidemia. Methods We administrated the data of 924,932 individuals insured under Gunma Prefecture’s National Health Insurance who underwent specific health checkups between 2011 and 2016. A logistic regression analysis was conducted to assess the association between the responses to 10 lifestyle questions and the future onset of lifestyle diseases. Results We examined 47,803 individuals who were not identified with lifestyle disorders at the initial checkup. In this study, weight gain of ≥10 kg since the age of 20 years showed the strongest association with MetS (OR: 2.01; 95% CI, 1.79–2.25). Additionally, smoking and weight gain were identified as common risk factors for MetS, hypertension, and dyslipidemia. The results revealed that lifestyle behaviors are longitudinally associated with the onset of lifestyle diseases. Conclusion The use of self-administered questionnaires to assess lifestyle behaviors can effectively predict future health risks.